The Reality of Indonesian Metrosexual Men's Online Skincare Shopping and the Power of Cultural Industry - Teguh Dwi Putranto (Universitas Merdeka Malang, 2023)
The purpose of this study is to find out the reality of metrosexual men's skincare shopping online which is driven by the power of the cultural industry. The research method in this study is virtual ethnography, which focuses on digital texts with Instagram as a medium for viewing the way in which metrosexual guys are disciplined. Six informants were identified by the researcher as part of the inquiry. Males, located in Jakarta, Bandung, and Surabaya, interested in facial skincare products, repeat purchasers, and visible via posts on their individual Instagram profiles are the characteristics of the informants in this study. The researcher used the snowball technique to conduct an informant search after obtaining informants who met the research criteria. The results of this study show that the reality of online skincare shopping driven by the power of the cultural industry for metrosexual men is carried out by metrosexual men with different practices. Besides that, the reality that has been built is that caring for facial skin is a form of self-respect and added value for everyone.Â Â